MOVEMENT OF LIQUIDS AND GASES (Proceedings of International Educators Conference, 2024)
This article explores the intricate dynamics of fluid flow, focusing on the movement of liquids and gases. Investigating the behavior of fluids is crucial in various fields, from engineering and physics to biology and environmental science. The study employs a comprehensive approach, encompassing literature analysis, methodology, results, and discussion, to provide a holistic understanding of fluid dynamics.